PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS X SMA NEGERI 1 MENGWI - I Dewa Putu Juwana; I Made Subrata; Dewa Ayu Widiasri (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
Student learning outcomes represent a key indicator of educational success, encompassing positive changes in knowledge, skills, attitudes, and behaviors acquired through instructional processes. However, low motivation and academic achievement in mathematics remain persistent challenges in many schools, including SMA Negeri 1 Mengwi. One promising approach to address these issues is the implementation of the Problem Based Learning (PBL) model, which actively engages students in inquiry, investigation, and concept construction through real-world problem solving. This study aims to examine the effect of the Problem Based Learning model supported by GeoGebra media on students’ motivation and mathematics learning outcomes in Grade X at SMA Negeri 1 Mengwi during the 2024/2025 academic year. The research employed a quasi-experimental method using a post-test only control group design. Two classes were randomly selected, with one assigned as the experimental group and the other as the control group. Data were collected using a motivation questionnaire and a mathematics achievement test. The results indicate that the application of the PBL model significantly enhances both student motivation and learning outcomes. The experimental group achieved a mean motivation score of 83.8 and a mathematics achievement score of 88.8, compared to 62.2 and 69.7 respectively in the control group. These findings suggest that PBL fosters curiosity, active participation, and deeper conceptual understanding more effectively than conventional teaching methods. Based on these results, the Problem Based Learning model is recommended as an alternative instructional strategy to improve the quality of mathematics education at the senior high school level, particularly in promoting student engagement and academic performance.